Assessment of changes in the burden of Chlamydia trachomatis infection in the context of widespread opportunistic chlamydia screening: Pgp3 seroprevalence measured in a series of nationally representative cross-sectional household surveys. (13th November 2015) - Woodhall, Sarah C; Wills, Gillian; Horner, Paddy; Craig, Rachel; Mindell, Jennifer S; Murphy, Gary; McClure, Myra; Soldan, Kate; Nardone, Anthony; Johnson, Anne M
Abstract: Background: Opportunistic screening of people aged under 25 years for genital Chlamydia trachomatis infection (chlamydia) was nationally implemented in England in 2008, but its impact is poorly understood. Antibodies to C trachomatis persist after infection, thus providing a marker of past infection. We aimed to explore the effect of screening on cumulative incidence of chlamydia (incidence of infection by a given age), as measured by C trachomatis antibodies. Methods: Anonymised serum samples from participants in the nationally representative Health Surveys for England (HSE) were tested for C trachomatis antibodies using two novel in-house Pgp3 ELISAs, which have demonstrated superior sensitivity to commercial assays. Determinants of being seropositive were explored with logistic regression among women (n=1402) and men (1119) aged 16–44 years in 2010–12 (years when questions about sexual behaviour were included in the survey). Seroprevalence trends among 16–24-year-old women (n=3361) were investigated over ten timepoints from 1994 to 2012. Findings: During 2010–12, Pgp3 seroprevalence among participants aged 16–44 years was 24·4% (95% CI 22·0–27·1) in women and 13·9% (11·8–16·2) in men. Seroprevalence increased with age (up to 33·5% [27·5–40·2] in 30–34-year-old women; 18·7% [13·4–25·6] in 35–39-year-old men) and with years since first sexual intercourse (38·2% [32·0–44·7] in women and 22·3% [16·2–29·8] in men aged 15–19 years). Total number of lifetime sexual partners and younger age at first sex were significantly associated with being seropositive (>10 lifetime sexual partners vs 1–4: odds ratio 3·84 women [95% CI 2·68–5·51], 5·95 men [3·41–10·35]; <16 years old at first sex vs >16: 2·26 women [1·61–3·16], 2·14 men [1·41–3·24]). 76·7% of seropositive 16–24-year-olds had never been diagnosed with chlamydia: among women, seroprevalence did not differ between the first (1994–96) and second (2001–02) periods sampled (prevalence ratio 1·04, 0·87–1·25); a non-significant decline was observed from 2008 to 2012 (prevalence ratio per year 0·94, 0·84–1·05). Interpretation: Our application of Pgp3 ELISAs demonstrates a high lifetime risk of chlamydia among women and that a large proportion of infections go undiagnosed. A decrease in age-specific cumulative incidence after national implementation of opportunistic chlamydia screening has not yet been demonstrated. We propose that these assays be used more widely to assess the effect of chlamydia control programmes. Funding: The Health Survey for England was funded by the Health and Social Care Information Centre. Testing of stored serum samples was funded by the Health Protection Agency (now Public Health England). The funders played no part in the design, conduct, analysis, or reporting of this study, or in the decision to submit the abstract for publication.